LEGISLATION AND IMPLICATIONS OF ARTICLE 54 PARAGRAPH (2) OF THE KUHP CONCERNING THE LAW OF PARDON IN CRIMINAL PROVISION IN INDONESIA - Debora Oktarina Sihombing; Yuliati; Bambang Sugiri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Law Number 1 of 2023 concerning the Criminal Code (KUHP) introduces the concept of rechterlijk pardon or judicial forgiveness in Article 54 paragraph (2). This provision grants judges discretionary authority to release perpetrators from criminal penalties by considering the severity of the act, the perpetrator's personal circumstances, or the circumstances after the crime, as long as they take into account a sense of justice and humanity. This article aims to analyze the legal ratio and practical implications of Article 54 paragraph (2) of the Criminal Code by reviewing the philosophical, sociological, and legal foundations of the birth of this norm. The research method used is normative juridical with a statutory, case, and comparative approach. The results of the study indicate that this provision is a correction to the overly rigid principle of legality while also opening up space for judges to balance legal certainty, justice, and expediency. The implication is that judges have broader discretion to uphold substantive justice, including integration with the values ​​of restorative justice. However, without clear technical guidelines, this provision has the potential to give rise to subjectivity and disparity in decisions. Therefore, the effectiveness of the application of Article 54 paragraph (2) of the Criminal Code is very dependent on the consistency of the judge's interpretation, the existence of implementing regulations, and adequate supervision.